"Against Medical Advice" Discharges Among HIV‐Infected Patients: Health and Health Services Outcomes. (January 2017) - Alfandre, David; Yang, Jingyan; Harwood, Katherine; Gordon, Peter; Lekas, Helen‐Maria; Chang, Steven J.; Yin, Michael T.
Abstract : N/A: Nurses are often first to identify and manage a patient leaving against medical advice (AMA), and so they are critical contributors to the development of strategies to address this problem. We studied AMA discharge in order to help develop useful interventions. We performed a cross‐sectional analysis of 55, 938 discharges from a single urban hospital for the years 2002‐2003 and 2012‐2013. AMA discharge rates were higher for HIV‐infected patients than for patients with alcohol‐related disorders or sickle cell anemia in both time periods, even after adjustment for age, race, sex, insurance status, and household income. For HIV infection, 25% of AMA discharges occurred in patients with multiple AMA discharges and 30‐day readmission rates were higher after an AMA discharge: odds ratio 1.57 (95% confidence interval 1.01 to 2.43, p = .046). Team‐based and nursing interventions that incorporate the treatment‐based values and preferences of HIV‐infected patients with prior AMA discharges may improve linkage to care and reduce readmissions.